Dwelling in the archive : women writing house, home, and history in late colonial India - Burton, Antoinette M., 1961- (Oxford University Press, 2003)
Through an analysis of the writings of three 20th century Indian women, this book explores how the memoirs, fictions, and histories written by women can be read as counter-narratives of colonial modernity.